Battery
By introducing an insulating film into the negative electrode material of the honeycomb structure of the lithium-ion battery, the structural collapse problem caused by the volume change of the negative electrode material is solved, the cycle characteristics of the battery and the initial charge and discharge efficiency are improved, and the structural stability and capacity balance are enhanced.
Patent Information
- Application Number
- JP2022143080
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-08
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2042-09-08
AI Technical Summary
The collapse of honeycomb structure caused by volume changes in the negative electrode material of existing lithium-ion batteries during charging and discharging affects the cycle characteristics and capacity balance of the battery, resulting in a decrease in charge and discharge efficiency.
A layer of insulating film with low insulating properties is introduced into the negative electrode material of the honeycomb structure, covering part of the inner wall and the outer surface, enhancing structural strength, and forming an insulating layer on the side walls by electrochemical methods to reduce the participation of the negative electrode active material in the charge and discharge reaction.
The cycle characteristics and primary charge and discharge efficiency of lithium-ion batteries are improved, the stability of the cellular structure is enhanced, and the capacity balance between the negative electrode and the positive electrode is improved.
Smart Images

Figure 0007626114000002 
Figure 0007626114000003 
Figure 0007626114000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to batteries. [Background technology]
[0002] JP 2020-123484 A (Patent Document 1) discloses a first electrode having a plurality of through holes and a second electrode filled in the through holes. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-123484 A Summary of the Invention [Problem to be solved by the invention]
[0004] Batteries using a honeycomb structure as a substrate are being considered. For example, a negative electrode composite material is formed into a honeycomb structure. A plurality of through holes are formed in the honeycomb structure. A separator layer is formed on the inner wall of the through hole. A positive electrode composite material is filled in the through hole except for the separator layer.
[0005] The negative electrode mixture contains a negative electrode active material. The negative electrode active material may expand and contract as the battery is charged and discharged. The honeycomb structure may collapse due to the volume change of the negative electrode active material. In order to improve the strength of the honeycomb structure, it is possible to thicken the outer periphery (side wall) of the honeycomb structure. When the outer periphery of the honeycomb structure is thickened, the amount of the negative electrode mixture is increased. The increase in the amount of the negative electrode mixture may disrupt the capacity balance between the negative electrode and the positive electrode. The disruption of the capacity balance may reduce the charge and discharge efficiency. Furthermore, the volume change (deformation) associated with the charge and discharge cycle may become locally large on the outer periphery of the honeycomb structure, which may promote the collapse of the honeycomb structure. In other words, there is room for improvement in the cycle characteristics.
[0006] An object of one aspect of the present disclosure is to improve cycle characteristics. [Means for solving the problem]
[0007] 1. A battery according to an aspect of the present disclosure includes a negative electrode composite, a separator layer, a positive electrode composite, and an insulating film. The negative electrode composite includes a negative electrode active material. The negative electrode composite forms a honeycomb structure. The honeycomb structure includes a first end face, a second end face, and a side wall. The second end face is the opposite face to the first end face. The side wall connects the first end face and the second end face. A plurality of through holes extending from the first end face to the second end face are formed. The separator layer covers at least a portion of the inner wall of the through hole. The separator layer separates the positive electrode composite from the negative electrode composite. The positive electrode composite includes a positive electrode active material. The positive electrode composite is disposed inside the through hole. The insulating film covers at least a portion of the outer surface of the side wall.
[0008] The insulating film includes an inactive material. In the present disclosure, "inactive material" refers to a material that has insulating properties and low reactivity with carrier ions (e.g., Li ions). It is considered that the portion of the honeycomb structure (negative electrode composite material) that is covered with the insulating film is inactivated and is less likely to participate in charge / discharge reactions. It is expected that the formation of the insulating film will improve the capacity balance between the negative electrode and the positive electrode. Furthermore, the insulating film can reinforce the side walls of the honeycomb structure. The reinforcing effect of the insulating film can reduce deformation of the honeycomb structure due to volumetric changes in the negative electrode active material. It is expected that the cycle characteristics will be improved by the synergistic effect of these actions.
[0009] 2. In the battery according to the above item "1," the insulating film may have a thickness of, for example, 5 μm or more. When the insulating film has a thickness of 5 μm or more, an improvement in the initial charge / discharge efficiency is expected.
[0010] 3. In the battery according to the above "1" or "2", the insulating film may contain at least one selected from the group consisting of polyimide (PI), polyamideimide (PAI), and polytetrafluoroethylene (PTFE). PI, PAI, and PTFE are inactive materials. Electrodeposition solutions containing PI and the like are relatively easily available on the market.
[0011] 4. The battery according to any one of the above items "1" to "3" may further include a negative electrode current collector. The outer surface of the side wall includes a first region and a second region. The insulating film covers the first region. The negative electrode current collector is joined to the second region.
[0012] A joint with the negative electrode current collector may be provided on a part of the side wall. In the present disclosure, the "negative electrode current collector" refers to a member that transfers electrons between the negative electrode mixture and the negative electrode current collector. The negative electrode current collector may be connected to an external terminal (negative electrode terminal). The negative electrode current collector may also function as an external terminal. The same applies to the positive electrode current collector.
[0013] 5. In the battery according to any one of the above items "1" to "4," the side wall may be porous. A part of the insulating film may penetrate into the pores of the side wall.
[0014] The honeycomb structure is a powder compact, and therefore may be porous. The insulating film may not only cover the outer surface of the side wall, but may also penetrate into the inside of the side wall. By inactivating a larger amount of the negative electrode active material, the initial charge / discharge efficiency is expected to be improved. Furthermore, the reinforcing effect is expected to be enhanced. As a method for infiltrating the inactive material into the pores of the side wall, for example, an electrodeposition method is considered.
[0015] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the present embodiment do not limit the technical scope of the present disclosure. The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are non-restrictive. The technical scope of the present disclosure encompasses all modifications within the meaning and scope equivalent to the description of the claims. For example, it is originally intended that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined.
[0016] Geometric terms (e.g., "parallel," "perpendicular," "orthogonal," etc.) should not be interpreted in a strict sense. For example, "parallel" may deviate slightly from the strict meaning of "parallel." Geometric terms may include, for example, tolerances, errors, etc. in design, work, manufacturing, etc. The dimensional relationships in each drawing may not match the actual dimensional relationships. To aid the reader's understanding, the dimensional relationships (length, width, thickness, etc.) in each drawing may be changed. Furthermore, some configurations may be omitted. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a schematic diagram showing an example of a battery according to the present embodiment. [Diagram 2] FIG. 2 is a schematic diagram of a power generating element in this embodiment. [Diagram 3] FIG. 3 is a schematic diagram showing an example of the negative electrode mixture in this embodiment. [Figure 4] FIG. 4 is a schematic cross-sectional view of the battery in this embodiment. [Diagram 5] FIG. 5 is a set of photographs showing the manufacturing process of the test battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] <Battery> FIG. 1 is a schematic diagram showing an example of a battery in this embodiment. The battery 100 is a Li-ion battery. However, the Li-ion battery is merely one example of the embodiment. The battery 100 includes a power generating element 50 and an insulating film 40. The battery 100 may further include, for example, a negative electrode current collector 15, a positive electrode current collector 25, an electrolyte (not shown), an exterior body (not shown), and the like. The exterior body may house the power generating element 50. The exterior body may be, for example, a metal container or a pouch made of a metal foil laminate film. The power generating element 50 may be impregnated with the electrolyte.
[0019] 2 is a schematic diagram of a power generating element in this embodiment. The power generating element 50 has a honeycomb structure as a base material. The power generating element 50 includes a negative electrode mixture 10 (honeycomb structure), a positive electrode mixture 20, and a separator layer 30.
[0020] 《Negative electrode mixture》 The negative electrode mixture 10 includes a negative electrode active material. The negative electrode active material may be a particle group. The negative electrode active material may have an average particle diameter of, for example, 1 to 30 μm. The "average particle diameter" refers to a particle diameter at which the cumulative frequency from the small particle diameter side reaches 50% in a volume-based particle diameter distribution. The average particle diameter is also written as "D50". The average particle diameter can be measured by a laser diffraction method. A numerical range such as "m to n%" includes an upper limit and a lower limit unless otherwise specified. That is, "m to n%" refers to a numerical range of "m% or more and n% or less". "m% or more and n% or less" includes "more than m% and less than n%".
[0021] The negative electrode mixture may further include, for example, a conductive material, a binder, and the like. The negative electrode mixture 10 may include, for example, 1 to 10% of a binder, 0 to 10% of a conductive material, and the remainder of the negative electrode active material, in mass fraction. The negative electrode active material may include any component. The negative electrode active material may include, for example, at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, hard carbon, silicon, silicon oxide, tin, tin oxide, and lithium titanate. The conductive material may include, for example, acetylene black (AB), carbon nanotubes (CNT), and the like. The binder may include, for example, styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), and the like.
[0022] FIG. 3 is a schematic diagram showing an example of the negative electrode composite in this embodiment. The negative electrode composite 10 is formed into a predetermined shape. The molded body may be porous. The negative electrode composite 10 may have any outer shape. The outer shape of the negative electrode composite 10 may be, for example, a columnar shape, a plate shape, or the like. The outer shape of the negative electrode composite 10 may be, for example, a cylindrical shape, a rectangular plate shape, or the like. The negative electrode composite 10 may have, for example, a diameter 10d. The diameter 10d indicates the maximum width in the XY plane. The diameter 10d may be, for example, 1 to 1000 mm. The negative electrode composite 10 may have, for example, a height 10h. The height 10h indicates the maximum width in the YZ plane. The height 10h may be, for example, 1 to 1000 mm. The ratio of the height 10h to the diameter 10d may be, for example, 0.1 to 10.
[0023] The negative electrode composite material 10 forms a honeycomb structure. The "honeycomb structure" may also be expressed as, for example, a "honeycomb core" or a "honeycomb molded body". The honeycomb structure (negative electrode composite material 10) includes a first end face 11, a second end face 12, and a side wall 13. The second end face 12 is the opposite face of the first end face 11. The second end face 12 may be parallel to the first end face 11 or may be non-parallel. The first end face 11 and the second end face 12 may each independently be a flat surface or a curved surface. The side wall 13 connects the first end face 11 and the second end face 12. The side wall 13 is formed around the entire periphery of the first end face 11 and the second end face 12.
[0024] A plurality of through holes 2 are formed in the negative electrode composite material 10. Each of the through holes 2 extends from the first end face 11 to the second end face 12. The extending direction of the through holes 2 may be parallel to the axial direction (Z-axis direction) of the negative electrode composite material 10. In a cross section perpendicular to the axial direction (XY plane), the through holes 2 may be arranged regularly or irregularly. The through holes 2 have openings in each of the first end face 11 and the second end face 12. The through holes 2 do not have openings in the side wall 13. In the XY plane, the through holes 2 are arranged at a density of, for example, 0.1 to 10 holes / mm. 2 The through holes 2 may be formed at a density of 100 to 300 μm. In the XY plane, the cross-sectional shape of the through holes 2 is arbitrary. The cross-sectional shape may be, for example, a square shape or a regular hexagon shape. The walls (parts of the negative electrode composite material 10) separating the through holes 2 from each other are also called "ribs". In the XY plane, the ribs may extend, for example, in a mesh shape. The ribs may have a thickness of, for example, 100 to 300 μm. The side walls 13 may be thicker than the ribs. For example, the thickness of the side walls 13 may be 2 to 10 times the thickness of the ribs.
[0025] <Separator layer> FIG. 4 is a schematic cross-sectional view of the battery in this embodiment. The separator layer 30 covers at least a part of the inner wall of the through hole 2. The separator layer 30 is interposed between the negative electrode composite 10 and the positive electrode composite 20. The separator layer 30 separates the positive electrode composite 20 from the negative electrode composite 10. The separator layer 30 has Li ion permeability. The separator layer 30 may be, for example, porous. The separator layer 30 may be permeated with an electrolytic solution. The separator layer 30 may have a thickness of, for example, 10 to 100 μm. The separator layer 30 includes an insulating material. The separator layer 30 may include, for example, a ceramic particle group, a resin particle group, a polymer gel, a solid electrolyte, or the like. The separator layer 30 may include, for example, boehmite, polyvinylidene fluoride (PVDF), PI, a sulfide solid electrolyte (Li3PS4), or the like.
[0026] The electrolyte contains a supporting electrolyte and a solvent. The supporting electrolyte may contain, for example, LiPF6. The solvent may contain, for example, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc.
[0027] <Positive electrode mixture> The positive electrode mixture 20 includes a positive electrode active material. The positive electrode active material may be a particle group. The positive electrode active material may have an average particle diameter of, for example, 1 to 30 μm. The positive electrode mixture 20 may further include, for example, a conductive material, a binder, and the like. The positive electrode mixture 20 may include, for example, 1 to 10% of a binder, 1 to 10% of a conductive material, and the remainder of the positive electrode active material, in mass fraction. The positive electrode active material may include any component. The positive electrode active material may include at least one selected from the group consisting of, for example, lithium cobalt oxide, lithium nickel oxide, lithium manganate, lithium nickel cobalt manganate, lithium nickel cobalt aluminate, and lithium iron phosphate. The conductive material may include, for example, AB, etc. The binder may include, for example, PVDF, etc. The positive electrode mixture 20 is disposed inside the through-hole 2. The positive electrode mixture 20 may be porous. The positive electrode mixture 20 may be filled inside the through-holes 2. The positive electrode mixture 20 may be, for example, columnar. A positive electrode current collector 25 may be joined to the tip of the positive electrode mixture 20. The positive electrode current collector 25 may include, for example, an Al foil.
[0028] 《Insulating film》 The insulating film 40 covers at least a part of the outer surface of the side wall 13. The insulating film 40 may cover the entire outer surface. The insulating film 40 may cover a part of the outer surface. The insulating film 40 can adjust the capacity balance between the negative electrode and the positive electrode by inactivating a part of the negative electrode active material. Furthermore, the insulating film 40 can reinforce the honeycomb structure.
[0029] The insulating film 40 includes an inactive material. The inactive material exhibits insulating properties. The inactive material has a concentration of, for example, 1×10 10 Ω cm or more, or 1×10 15The insulating film 40 may have a volume resistivity of Ω·cm or more. Furthermore, the inactive material is not substantially involved in charge / discharge reactions (Li ion insertion and desorption reactions). The insulating film 40 may contain, for example, a resin particle group. The resin particle group may have an average particle diameter of, for example, 0.001 to 1 μm. The insulating film 40 may contain, for example, at least one type selected from the group consisting of PI, PAI, and PTFE.
[0030] The insulating film 40 may have a thickness of, for example, 1 to 100 μm, or 3 to 50 μm. The insulating film 40 may have a thickness of, for example, 5 μm or more. When the insulating film 40 has a thickness of 5 μm or more, an improvement in the initial charge / discharge efficiency is expected. The insulating film 40 may have a thickness of, for example, 6 μm or more, 7 μm or more, or 8 μm or more. The insulating film 40 may have a thickness of, for example, 12 μm or less, or 10 μm or less.
[0031] A part of the inactive material may penetrate into the pores of the side wall 13. By inactivating a larger amount of the negative electrode active material, an improvement in the initial charge / discharge efficiency is expected. Furthermore, an enhancement in the reinforcing effect is also expected. For example, the resin particle group may be distributed in a range of 0.1 to 20 μm or 0.5 to 2.5 μm from the outer surface of the side wall 13 in the depth direction.
[0032] The insulating film 40 may be formed by any method. For example, the insulating film 40 may be formed by electrostatic spraying, dipping, or electrodeposition. The electrodeposition method tends to form a thin and uniform insulating film 40 compared to the electrostatic spraying, dipping, and other methods. Furthermore, the electrodeposition method tends to allow the inactive material to easily penetrate into the pores of the sidewall 13. After electrodeposition, the insulating film 40 may be heat-treated to fuse the resin particles together.
[0033] 《Negative electrode current collector》 The negative electrode current collector 15 is bonded to the negative electrode composite material 10. The negative electrode current collector 15 may be bonded to, for example, a part of the outer surface of the side wall 13. For example, the outer surface of the side wall 13 may be divided into a first region 13a and a second region 13b. The first region 13a may be covered with an insulating film 40. The negative electrode current collector 15 may be bonded to the second region 13b. For example, in the axial direction (Z-axis direction) of the honeycomb structure, the negative electrode current collector 15 may be disposed at the center of the honeycomb structure. By disposing the negative electrode current collector 15 at the center, the current passing distance is shortened, and it is expected that the battery resistance is reduced. The negative electrode current collector 15 may be separated from the upper end or lower end (the first end face 11 or the second end face 12) of the side wall 13 by 0.5 mm or more. By separating the negative electrode current collector 15 from the positive electrode composite material 20, it is expected that the short circuit resistance is improved. The distance between the upper end or lower end of the side wall 13 and the negative electrode current collector 15 may be, for example, 0.5 to 5 mm or 0.5 to 2 mm. The negative electrode current collector 15 may include, for example, a metal foil, a metal wire, a metal mesh, or the like. The negative electrode current collector 15 may be formed of, for example, a metal that is difficult to alloy with Li. The negative electrode current collector 15 may include, for example, Cu, Ni, stainless steel, or the like. EXAMPLES
[0034] <Production of test batteries> Test batteries No. 1 to 10 were produced as follows. Hereinafter, for example, "test battery No. 1" may be abbreviated as "No. 1."
[0035] No.1 (Honeycomb structure molding) The following materials were prepared: Negative electrode active material: natural graphite (average particle size: 15 μm) Binder: CMC Dispersion medium: Ion-exchanged water
[0036] A negative electrode paste was prepared by mixing 100 parts by mass of a negative electrode active material, 10 parts by mass of a binder, and 60 parts by mass of a dispersion medium. The negative electrode paste was extruded from a mold to form a molded body. The molded body was dried at 120°C for 3 hours to form a honeycomb structure. The honeycomb structure had the following structure.
[0037] Shape: Cylindrical (diameter: 20mm, height: 20mm) Arrangement of through holes: equally spaced, regular (honeycomb) Cross-sectional shape of through hole: regular hexagon (length of one side: 700 μm, rib thickness: 200 μm)
[0038] (Insulating film formation) A heat shrink tube (hereinafter, may be abbreviated as "tube") having a width of 3 mm was wound in a strip shape around the center of the side wall of the honeycomb structure. The tube was heated to adhere to the side wall. The tube was a masking material. A negative electrode current collector was later bonded to the location where the tube was placed. A lead wire (made of Ni, 30 μm thick, 5 cm long) was sandwiched between the honeycomb structure and the tube. The first end face and the second end face were covered with paraffin film. The paraffin film prevents the electrodeposition liquid from penetrating into the through holes. The honeycomb structure was immersed in an electrodeposition liquid for polyimide film (product name "Elecoat PI", manufactured by Shimizu Corporation). An electric current was passed through the lead wire led out from the liquid surface to carry out the electrodeposition treatment. In the electrodeposition treatment, the honeycomb structure was used as the cathode (-), and a potential difference of 30 V was applied. The treatment time was 1 minute. An insulating film was formed on the outer surface of the side wall of the honeycomb structure by the electrodeposition process. The insulating film was composed of a group of PI particles. After the electrodeposition process, the lead wires, tubes and paraffin film were removed from the honeycomb structure. The honeycomb structure was washed with water to remove excess electrodeposition liquid. After washing with water, the honeycomb structure was subjected to heat treatment in a vacuum drying furnace. The heat treatment temperature was 190°C, the heat treatment time was 30 minutes, and the heat treatment atmosphere was a vacuum atmosphere. The insulating film was fixed by the heat treatment. From the increase in diameter of the honeycomb structure, the thickness of the insulating film was determined to be 8 μm.
[0039] FIG. 5 is a photograph showing the manufacturing process of the test battery. The honeycomb structure includes a side wall 13. The outer surface of the side wall 13 includes a first region 13a and a second region 13b. In the axial direction of the honeycomb structure, the second region 13b is sandwiched between two first regions 13a. The first region 13a and the second region 13b each surround the side wall 13. The first region 13a is covered with an insulating film 40 by the electrodeposition process. The second region 13b is masked by a tube, so that the insulating film 40 is not formed during the electrodeposition process. After the electrodeposition process, the negative electrode current collector 15 is joined to the second region 13b.
[0040] (Formation of separator layer) The following materials were prepared: Insulating material: Boehmite (average particle size: 0.5 μm) Binder: PVDF (product name KF Polymer, grade #8500, manufactured by Kureha Corporation) Dispersion medium: NMP
[0041] A separator paste was prepared by mixing 57 parts by mass of an insulating material, 5 parts by mass of a binder, and 38 parts by mass of a dispersion medium. 3 to 5 g of the separator paste was placed on a first end face of a honeycomb structure. A vacuum pump sucked the separator paste into the through holes from the second end face side. This caused the separator paste to adhere to the inner walls of the through holes. The honeycomb structure was dried at 120°C for 15 minutes. This resulted in the formation of a separator layer (boehmite layer). The average thickness of the separator layer was measured by cross-sectional observation using an optical microscope. The average thickness was 65 μm.
[0042] An electrodeposition liquid (product name "Elecoat PI", manufactured by Shimizu Corporation) was prepared. The electrodeposition liquid contained boehmite particles (average particle diameter: 0.5 μm) and PI particles as dispersoids. A Ni flat wire (thickness: 50 μm, width: 3 mm) was prepared. The Ni flat wire was wound around the side wall of the honeycomb structure. The Ni flat wire was connected to a power source. The honeycomb structure was immersed in the electrodeposition liquid. The honeycomb structure was made the cathode (-) and the working electrode was made the anode (+), and a potential difference of 30 V was applied for 2 minutes. As a result, the first end face and the second end face were covered with the separator layer (PI layer). After electrodeposition, the honeycomb structure was washed with water to remove excess electrodeposition liquid. After washing, the honeycomb structure was heat-treated at 180°C for 1 hour.
[0043] (Positive electrode mixture placement) The following materials were prepared: Positive electrode active material: Lithium cobalt oxide (average particle size: 10 μm) Conductive material: Acetylene black Binder: PVDF (product name: KF Polymer, grade #1300, manufactured by Kureha Corporation) Dispersion medium: NMP
[0044] A positive electrode paste was prepared by mixing 64 parts by mass of a positive electrode active material, 4 parts by mass of a conductive material, 2 parts by mass of a binder, and 30 parts by mass of a dispersion medium. A plastic pipe was prepared. The pipe had an inlet end and an outlet end. A honeycomb structure was fixed to the outlet end side. A plate-shaped metal filter was prepared. The pipe was fixed upright on the metal filter. The outlet end was in contact with the metal filter. 3.5 g of positive electrode paste was injected from the inlet end of the pipe. A cylinder (round bar) was inserted into the pipe from the inlet end. The cylinder had a diameter (body diameter) approximately the same as the inner diameter of the pipe. The cylinder was pressed with a pressing force of 300 N. This forced the positive electrode paste into the through hole. When the pressing force exceeded 500 N, the pressing of the cylinder was stopped. The honeycomb structure was removed from the pipe. The honeycomb structure was vacuum dried at 120° C. for 30 minutes. As a result, the positive electrode mixture was disposed inside the through-hole.
[0045] (Arrangement of current collectors) An Al foil (diameter: 15 mm, thickness: 15 μm) was prepared as a positive electrode current collector. At each of the first end face and the second end face, the positive electrode current collector was bonded to the tip of the positive electrode composite material with 0.5 g of positive electrode paste. After the positive electrode current collector was placed, the honeycomb structure was dried at 120° C. for 15 minutes.
[0046] A Ni flat wire (thickness: 50 μm, width: 3 mm) was prepared as a negative electrode current collector. The negative electrode current collector was wrapped around the area that had been masked with the tube during the electrodeposition process.
[0047] Stainless steel lead tabs were prepared as external terminals, and the lead tabs were welded to the positive electrode current collector and the negative electrode current collector, respectively.
[0048] (Injection) A pouch made of an aluminum laminate film was prepared as an exterior body. A honeycomb structure was housed in the exterior body. 5 g of an electrolyte was poured into the exterior body. The electrolyte had the following composition. The exterior body was vacuum sealed so that the lead tab was led out to the outside of the exterior body. A test battery was manufactured in the above manner.
[0049] (Electrolyte composition) Supporting electrolyte: LiPF6 (concentration: 1mol / kg) Solvent: EC / EMC / DMC=1 / 1 / 1 (volume ratio)
[0050] (Measurement of initial charge / discharge efficiency) The following charging, resting, and discharging were performed in sequence. "CC" indicates constant current mode, "CV" indicates constant voltage mode, and "CCCV" indicates constant current-constant voltage mode. The initial charge / discharge efficiency was calculated by dividing the initial discharge capacity by the initial charge capacity.
[0051] Charging: CCCV, CC current = 40mA, CV voltage = 4.2V, final current = 4mA Pause: 10 minutes Discharge: CCCV, CC current = 40mA, CV voltage = 3V, final current = 4mA
[0052] (Cycle test) 100 charge / discharge cycles were performed, with one cycle consisting of the following cycle of charge, rest, and discharge. The number of cycles at which short circuit behavior was detected was confirmed. The more cycles required to detect short circuit behavior, the better the cycle characteristics are considered to be.
[0053] Charging: CCCV, CC current = 200mA, CV voltage = 4.2V, final current = 10mA Pause: 10 minutes Discharge: CC, CC current = 200mA, final voltage = 3V
[0054] No.2, 3, 7 The thickness of the insulating film was changed by changing the potential difference during the electrodeposition process (see Table 1 below). Except for this, test cells were fabricated in the same manner as No. 1.
[0055] No.4 In the "Formation of Insulating Film", an electrodeposition liquid for polytetrafluoroethylene film (manufactured by Shimizu Corporation) was used instead of an electrodeposition liquid for polyimide film (manufactured by Shimizu Corporation). In the electrodeposition process, the honeycomb structure was used as the anode (+) and a potential difference of 25 V was applied. The process time was 1 minute. By the electrodeposition process, an insulating film was formed on the outer surface of the side wall of the honeycomb structure. The insulating film was composed of a group of PTFE particles. Except for these, a test battery was manufactured in the same manner as No. 1.
[0056] No.5, 6, 8 The thickness of the insulating film was changed by changing the potential difference during the electrodeposition process (see Table 1 below). Except for this, test cells were fabricated in the same manner as No. 4.
[0057] No.9 No electrodeposition was performed, and instead, a PI tape ("Kapton (registered trademark) tape", thickness 50 μm) was attached to the side wall of the honeycomb structure. In No. 9, the PI tape was the insulating film. The attachment position of the PI tape was almost the same as the formation position of the insulating film in No. 1. Except for this, the test battery was manufactured in the same manner as No. 1.
[0058] No.10 A test cell was constructed similar to No. 1, except that no insulating film was formed.
[0059] [Table 1]
[0060] <Result> There is a tendency that the cycle characteristics improve due to the formation of the insulating film on the outer wall of the honeycomb structure (comparison of Nos. 1 to 9 with No. 10).
[0061] There is a tendency that the initial charge / discharge efficiency improves when the insulating film has a thickness of 5 μm or more (comparison of Nos. 1 to 3 with No. 7, and comparison of Nos. 4 to 6 with No. 8).
[0062] Compared to the electrochemically deposited film (No. 1, etc.), the PI tape (No. 10) tends to have a smaller improvement in cycle characteristics and initial charge / discharge efficiency. Unlike the electrochemically deposited film, the PI tape is thought to not penetrate into the pores of the side walls. Compared to the electrochemically deposited film, the PI tape is thought to have a smaller reinforcing effect on the honeycomb structure. [Explanation of symbols]
[0063] 2 through hole, 10 negative electrode composite material, 10d diameter, 10h height, 11 first end surface, 12 second end surface, 13 side wall, 13a first region, 13b second region, 15 negative electrode current collector, 20 positive electrode composite material, 25 positive electrode current collector, 30 separator layer, 40 insulating film, 50 power generating element, 100 battery.
Claims
1. A negative electrode mixture, a separator layer, a positive electrode mixture, and an insulating film Including, The negative electrode mixture contains a negative electrode active material, The negative electrode mixture forms a honeycomb structure, The honeycomb structure includes a first end face, a second end face, and a side wall, the second end surface is an opposite surface to the first end surface, the side wall connects the first end surface and the second end surface, A plurality of through holes are formed extending from the first end surface to the second end surface, the separator layer covers at least a portion of an inner wall of the through hole, the separator layer separates the positive electrode mixture from the negative electrode mixture; The positive electrode mixture contains a positive electrode active material, The positive electrode mixture is disposed inside the through hole, and The insulating film covers at least a portion of an outer surface of the side wall. battery.
2. The insulating film has a thickness of 5 μm or more.
10. The battery of claim 1.
3. The insulating film includes at least one selected from the group consisting of polyimide, polyamideimide, and polytetrafluoroethylene. The battery according to claim 1 or 2.
4. Further comprising a negative electrode current collector, the outer surface of the sidewall includes a first region and a second region; The insulating film covers the first region, and The negative electrode current collector is joined to the second region. The battery according to claim 1 or 2.
5. the sidewall is porous; A portion of the insulating film penetrates into the pores of the sidewall. The battery according to claim 1 or 2.
Citation Information
Patent Citations
Secondary battery and method of manufacturing the same
JP2020123484A
Battery
JP2022014064A
Battery
JP2022022761A
Method for manufacturing electrode active material molding for lithium-ion battery and method for manufacturing lithium-ion battery
WO2018194163A1